Characterization of an ascorbate-reducible cytochrome b561 by site-directed mutagenesis - Bérczi, Alajos; Asard, Han (Acta Biologica Szegediensis, 2006)
Ascorbate(ASC)-reducible cytochrome b561 (Cyt-b561) proteins are present in both plants and animals and create a well-distinguished protein family amongst the two-heme containing b-type cytochromes. One isoform of the Cyts-b561 identified by genomic analysis of Arabidopsis thaliana has been localized in the tonoplast. We have expressed the tonoplastlocalized Cyt-b561 (TCyt-b561) in yeast (Saccharomyces serevisiae) cells and shown that the biophysical properties of the recombinant TCyt-b561 is very similar to those of the chromaffin granule Cyt-b561 (CGCyt-b561). Mutation of 4 well-conserved histidine residues (H50, H83, H117, H156) resulted in different expression levels and revealed the importance of these 4 His residues in heme binding and protein expression. Modification of the protein by FLAG-tag or His6-tag resulted in different degrees of reduced expression levels. When all lysine residues (K70, K76, K79, K80, and K159) in the vicinity of the putative ASC-binding motive were one-by-one replaced by alanine, no major changes in the expression levels were observed. Except in case of the K80A mutant, where the low-affinity ASC-binding constant increased significantly, there were no significant changes in either kinetic parameter characterizing the bi-phase ASC-dependent reduction of TCytb-b561. These observations are discussed in comparison to properties of the recombinant CGCyt-b561.